Effect of antiretroviral drugs on the pharmacodynamics of gliclazide with respect to glucose–insulin homeostasis in animal models - S K Mastan; K Eswar Kumar (Dove Medical Press, 2009)
S K Mastan1, K Eswar Kumar21Research and Development Cell, Jawaharlal Nehru Technological University, Hyderabad, Andhra Pradesh, India; 2Pharmacology Division, AU College of Pharmaceutical Sciences, Andhra University, Visakhapatnam, Andhra Pradesh, IndiaAbstract: The objective of this study was to investigate the effect of oral administration of antiretroviral drugs (indinavir, ritonavir, atazanavir, efavirenz and nevirapine) on the pharmacodynamics of gliclazide in rats (normal and diabetic) and rabbits with respect to glucose–insulin homeostasis to evaluate the safety and effectiveness of the combinations. Blood samples were collected at regular time intervals in rats from retro orbital puncture and by marginal ear vein puncture in rabbits. All the blood samples were analyzed for blood glucose by glucose oxidase–peroxidase method and insulin by a radio immuno assay method. The insulin resistance index and β-cell function were determined by a homeostasis model assessment. Indinavir and ritonavir alone had significant impact on glucose–insulin homeostasis in animal models among the antiretroviral drugs used in our study. In combination, indinavir and efavirenz significantly reduced the activity of gliclazide, while ritonavir and atazanavir significantly increased the activity of gliclazide. However, nevirapine had no significant effect on the activity of gliclazide. From this study we conclude that glucose–insulin homeostasis disorders associated with antiretroviral drugs are not class-specific, but are drug-specific. So care should be taken when indinavir, ritonavir, atazanavir and efavirenz are prescribed for diabetic patients.Keywords: protease inhibitors, efavirenz, nevirapine, gliclazide, homeostasis model assessment, diabetes